Electric control of the bandgap in quantum wells with band-inverted junctions. (2nd November 2017) - Díaz-Fernández, A; Chico, Leonor; Domínguez-Adame, F
Abstract: In IV–VI semiconductor heterojunctions with band-inversion, such as those made of P b 1 − x S n x Te or P b 1 − x S n x Se, interface states are properly described by a two-band model, predicting the appearance of a Dirac cone in single junctions. However, in quantum wells the interface dispersion is quadratic in momentum and the energy spectrum presents a gap. We show that the interface gap shrinks under an electric field parallel to the growth direction. Therefore, the interface gap can be dynamically tuned in experiments on double-gated quantum wells based on band-inverted compounds.